2013
DOI: 10.1044/1092-4388(2012/11-0338)
|View full text |Cite
|
Sign up to set email alerts
|

Speech Perception in Noise by Children With Cochlear Implants

Abstract: Purpose Common wisdom suggests that listening in noise poses disproportionately greater difficulty for listeners with cochlear implants (CIs) than for peers with normal hearing (NH). The purpose of this study was to examine phonological, language, and cognitive skills that might help explain speech-in-noise abilities for children with CIs. Method Three groups of kindergartners (NH, hearing aid wearers, and CI users) were tested on speech recognition in quiet and noise and on tasks thought to underlie the abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
89
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 59 publications
8
89
0
1
Order By: Relevance
“…As Caldwell and Nittrouer (2013) note, voicing contrasts for consonants may be relatively more resistant to hearing loss than other phonemic distinctions, a fact that has likely contributed to the results we found regarding how well bilingual children with CIs were able to match their peers' productions when it came to initial stop voicing. Future studies on phonological acquisition in bilingual children with hearing loss who use CIs may focus on a wider range of phonological phenomena, some of which are easily accessible to children with CIs and others that may be more challenging for them (such as certain fricatives; cf.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…As Caldwell and Nittrouer (2013) note, voicing contrasts for consonants may be relatively more resistant to hearing loss than other phonemic distinctions, a fact that has likely contributed to the results we found regarding how well bilingual children with CIs were able to match their peers' productions when it came to initial stop voicing. Future studies on phonological acquisition in bilingual children with hearing loss who use CIs may focus on a wider range of phonological phenomena, some of which are easily accessible to children with CIs and others that may be more challenging for them (such as certain fricatives; cf.…”
Section: Discussionmentioning
confidence: 64%
“…We also posit the null hypothesis regarding group differences between bilingual children with CIs versus their peers with NH because as Caldwell and Nittrouer (2013) note, VOT can be conveyed well via the device, but as reviewed in previous paragraphs, children with CIs may display delay in some aspects of language relative to their peers with NH. Thus, it is not known whether bilingual children with CIs will produce stop voicing contrasts in a similar fashion to their peers with NH due to the perceptual salience of the contrast or whether there will be differences due to hearing loss.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous research has clearly demonstrated the benefit of a good SNR for speech understanding in children [Caldwell and Nittrouer, 2013;Gifford et al, 2011;Meister et al, 2015;Plasmans et al, 2016]. The use of hearing assistance technology for CI patients is therefore essential to improve speech recognition in classrooms.…”
Section: Exposure Environmentsmentioning
confidence: 99%
“…Fewer studies have sought to explore how these cognitive abilities relate to the development of PhPS [30]. Another aspect worth considering when studying DHH children's cognitive development is how reduced spectral resolution [31] and less cues of temporal fine structure [32,33] affect how they develop PhPS in different situations, i.e., speech recognition in noise [21,34], and in reaching fine-grained levels of phonological sensitivity [2]. Thus, as Nittrouer et al reasoned [2] finegrained levels of phonological processing might be difficult to acquire both due to the hearing loss itself, and due to the signal transmitted through their technical device.…”
Section: Introductionmentioning
confidence: 99%